2016
DOI: 10.5935/1518-0557.20160030
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of blood borne viruses in IVF: an audit of a fertility Centre

Abstract: Objective The rate of infertility continues to be on the increase in the developing world. Similarly, the rates of blood-borne viral infections (BBVs) such as Human Immunodeficiency Virus (HIV), Hepatitis B virus (HBV) and Hepatitis C virus (HCV) are also on this rise. In 2014, the World Health Organization (WHO) quoted prevalences of 1.5% (HIV), 15% (HBV) 1.3 - 8.4% (HCV) in the Ghanaian general population. It has been reported that BBVs can adversely affect male fertility, specifically sperm count and progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
1
6
1
Order By: Relevance
“…Kye-Duodu et al (2016) also found no significant association in HBV infection among PLHIV from rural and urban areas in the Eastern Region of Ghana but in the same study, HBV infection was found to be significantly higher in adults (≥18 years). In the Ghanaian general population, HBV infection was reported to be significantly higher in men than women [16] which is contrary to the result of this study. A study from Rwanda also found discordant relationship where older age was associated with HBV infection, but gender was not associated with infection [29].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Kye-Duodu et al (2016) also found no significant association in HBV infection among PLHIV from rural and urban areas in the Eastern Region of Ghana but in the same study, HBV infection was found to be significantly higher in adults (≥18 years). In the Ghanaian general population, HBV infection was reported to be significantly higher in men than women [16] which is contrary to the result of this study. A study from Rwanda also found discordant relationship where older age was associated with HBV infection, but gender was not associated with infection [29].…”
Section: Discussioncontrasting
confidence: 99%
“…HIV uninfected individuals) where the seroprevalences in most cases ranged from 6.94 to 15.8% for HBsAg and 1.84 to 8.4% for HCV [1417, 19]. Only two studies reported lower seroprevalences, 5.5% for HBsAg [18] and 0.4% for HCV [16]. Comparing the HBV and HCV results of this current study to previous reports of studies conducted in Ghana and other sub-Sahara African countries [2224, 26] it could be observed that HBV seroprevalence is higher than HCV seroprevalence in the Ghanaian population and the sub-Sahara African countries.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, the prevalence of HIV is 173/100,000 population (Haddad et al, 2019). In higher prevalence countries, rates in fertility clinics were found to be 1.7% (HIV), 7.9% (HBV) and 0.4% (HCV), similar to reported rates in their general populations (Yakass et al, 2016). exposure-prone procedures even though infected, undiagnosed surgeons pose a risk to patients through bloodborne contamination.…”
Section: Managing Cross-contamination With Testing Frequencysupporting
confidence: 74%
“…These data constitute the first report of HIV prevalence among the infertile population in Hunan, China. The overall prevalence of HIV during 2012–2018 in China was 0.04% (129/338432), a relatively low epidemic level, which is different from the reported 0.0046%(2/43274) among infertile couples in Royan[ 29 ],1.7% (4/229)among recruited couples in Ghana[ 30 ], and 16.8% of primary infertile couples (women, 24/135; men, 19/121) and 35.5% of secondary infertile couples (women,74/177; men,36/133) in Rwanda[ 31 ]. We believed that the relatively high prevalences in these studies are related to their small sample sizes.…”
Section: Discussionmentioning
confidence: 82%